(untitled) (Research, Society and Development, 2021)
An alternative to reduce the use of degradable polymers is biopolymers. Among them, poly (3-hydroxybutyrate) - PHB stands out, which is a biodegradable semicrystalline thermoplastic obtained from natural renewable sources. In this context, PHB / PEG blends with 0, 5, 10 and 15% w/w of orange essential oil were developed using the solution casting technique. The films were characterized by medium infrared, Principal Component Analysis and mechanical properties. The components present in the orange essential oil were identified by mass spectrometry by gas chromatography and the disk diffusion method was used to evaluate the antimicrobial activity. The results showed that the major component in orange essential oil is d-limonene and that it has antimicrobial activity against the bacteria S. aureus and E. coli. The presence of the major component in the PHB / PEG blend was also confirmed by FTIR / PCA. The mechanical results showed that the additives of 10% and 15% w/w made the films more mechanically resistant and with greater rigidity. PHB/PEG/OEL films have shown the potential to be applied as antimicrobial food packaging.